Anti-inflammatory actions of intravenous immunoglobulin. - Nimmerjahn, Falk; Ravetch, J. V. (Annual Review of Immunology, 2008)
The remarkable success story of the therapeutic application of pooled immunoglobulin G (IgG) preparations from thousands of donors, the so-called intravenous IgG (IVIG) therapy, to patients with a variety of hematological and immunological disorders began more than half a century ago. Since then, the use of this primary blood product has increased constantly, resulting in the serious danger of shortages in supply. Despite its widespread use and therapeutic success, the mechanisms of action, especially of the anti-inflammatory activity, are only beginning to be understood. In this review, we summarize the clinical use of IVIG for different diseases and discuss recent data on the molecular mechanisms that might explain how this potent drug mediates its activity in vivo.